(untitled) (Journal of Hama University, 2021)
This study is considered to be one of the quantitative, analytical and epidemiological studies. Data were collected from previous records of the (GCO) General Cattle Organisation (Jub Ramla- Fedio- AL Mukhtaria) for the last ten years (2008 - 2018) were included, in order to figure out the reasons of some health problems of cattle, especially those related to production diseases (Mastitis – Brucellosis- Milk Fever – Lameness – Postnatal lochometritis) Obvious and substantial alterations were found in the spreading of Mastitis and lameness in all cattle farms between summer and winter as risk factors of the risk factors of mastitis and Lame diseases. Other risk factors which gave significant alterations were old age, periodix examination of the udder gland and the hygiene of barns. It also became apparent that the recursion of mastitis during one milk production cycle lead to the loss of approximately 170 SP.For each /100/ cases. As for brucellosis, cases were reported in Fedio and AL Mukhtaria stations, while Jub Ramla farm was free of any cases using the rapid based on test carriedout by(GCO). Results of analytical study showed no substantial alternations in the occurrence of milk fever since the first season till the tenth birth in some of the cattle, and results showed that upon first birth there is a substantial correlation between the number of insemination and milk production for the duration of /100/ days.